MO408OBSTRUCTIVE NEPHROPATHY - STILL PREVALENT DISEASE. (29th May 2021) - Bulatovic, Ana; Todorov Sakic, Verica; Djuric, Petar; Bjedov, Jelena; Jankovic, Aleksandar; Naumovic, Radomir; Dimkovic, Nada
Abstract: Background and Aims: Acute kidney injury (AKI) secondary to urinary obstruction is a common urological-nephrological problem. In this retrospective study, our goals were to describe the etiology, management and outcomes of patients with obstructive nephropathy who were hospitalized at Nephrology Department during 2019. Method: AKI was defined by the RIFLE classification. Diagnosis of obstruction was defined by ultrasound imaging, intravenous pyelography and CT scan. Results: During 2019 AKI secondary to urinary obstruction was diagnosed to 64 patients. 73% of them were male, average age 65 ± 16 years. About 60% of the patients had bilateral hydronephrosis, chronic kidney disease and anuria duration longer than 24h. The following desobstructive procedures were applied: urinary catheterization to 33 patients, percutaneous nephrostomy tube to 14 patients, double-J stent to 7 and other procedures to 10 patients. The most common causes of obstruction were malignancy and benign prostatic hyperplasia 60%, calculosis 17%, and other causes 20% such as neurogenic bladder and retroperitoneal fibrosis. As many as 30% of patients required acute hemodialysis treatment, of which 6% remained on a chronic program in period of three months. Out of all, 30% of patients had a partial recovery of kidney function, while 20% had complete recovery. The most common complication was infection and bleeding. The univariate logistic regression, adjusted for age and hemodialysis treatment, has shown that significant independent predictors for chronic kidney disease progression were anuria duration >24h (RR 2.21; 95% CI 0.014-1.03; p=0.05), polyuria duration (RR 2.11; 95% CI 1.112-3.98; p=0.02) and duration of hospital treatment (RR 9.16; 95% CI 2.102-39.94; p=0.03). The most significant predictor of death was duration of hospital treatment (RR 9.16; 95% CI 2.102-3.399; p=0.003). Multivariate logistic regression did not shown significance any of the above risk factors. Conclusion: Given that third of patients with obstructive nephropathy require acute HD, 6% remain in chronic HD, and almost one third require rehospitalization, close cooperation between a nephrologist and urologist is required. Rapid desobstructive procedures and careful monitoring after desobstruction is warranted. Requirement of regular screening remains opened for obstruction in vulnerable populations.